Design method of dual phase Hy-Vo silent chain transmission system - Cheng, Yabing (Strojniški vestnik, 2015)
Based on the theory that the Hy-Vo silent chain meshes with the sprocket, and the related condition that the Hy-Vo silent chain sprocket meshes with a tool, multi-variations of the Hy-Vo silent chain and sprocket are designed. The meshing design system of the dual phase Hy-Vo silent chain plate-sprocket-tool is built. The design method of the dual phase Hy-Vo silent chain transmission system is presented. Combined with a concrete example, the dual phase Hy-Vo silent chain transmission system model is established, and the dual phase transmission system is decomposed into two single-phase transmission systems. The research shows that the instantaneous transmission ratio of a dual phase transmission system may be different from the instantaneous transmission ratio of a decomposed single-phase transmission system. If the two pitches of the dual phase sprocket are equal and the two groups of pressure angles are the same, the largest fluctuation quantity of the dual phase transmission system is less in comparison with the single-phase transmission system, and the polygon effect is smaller. The design method will provide a corresponding theoretical guidance for the design of other multi-phase chain systems.
Keywords: dvofazni prenosniki; fluktuacije; multivariabilnost; poligonski efekt; snovanje sistema ubiranja; tiha veriga Hy-Vo